2011
DOI: 10.1063/1.3626845
|View full text |Cite
|
Sign up to set email alerts
|

Strong terahertz radiation by beating of spatial-triangular lasers in a plasma

Abstract: Resonant excitation of terahertz (THz) radiation by beating of two spatial-triangular laser beams having different frequencies and wave numbers but the same electric fields is proposed, where the ponderomotive force in the transverse direction is realized due to the beating and spatial variation of the lasers’ fields. This gives rise to a stronger transient transverse current due to a sharp gradient in the laser field, and subsequently THz radiation is excited resonantly in the presence of a periodic density s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Therefore, recently significant efforts have been focused on studying the effects of different laser and plasma parameters on THz generation in the laser-plasma interaction scheme. [17] Furthermore, Singh et al [18] have applied two cosh-Gaussian lasers as THz radiation source and observed notable changes in THz power as well as conversion efficiency. [9][10][11][12] In fact, the ponderomotive force of laser pulse imparts an oscillatory velocity to the electrons so that as a result of proper phase matching with periodically modulated density plasma, THz waves will be emitted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, recently significant efforts have been focused on studying the effects of different laser and plasma parameters on THz generation in the laser-plasma interaction scheme. [17] Furthermore, Singh et al [18] have applied two cosh-Gaussian lasers as THz radiation source and observed notable changes in THz power as well as conversion efficiency. [9][10][11][12] In fact, the ponderomotive force of laser pulse imparts an oscillatory velocity to the electrons so that as a result of proper phase matching with periodically modulated density plasma, THz waves will be emitted.…”
Section: Introductionmentioning
confidence: 99%
“…[21] THz amplification based on four-wave coupling in a plasma has been investigated. [36] They also studied THz generation by beating of two spatial-triangular [37] and rounded triangular laser beams in a rippled density plasma in the presence of an external transverse magnetic field. [23] THz radiation generation via a filamentation process has been proposed through many theoretical analyses and laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[65] Singh et al have reported THz generation by mixing two cosh-Gaussian laser beams in a density rippled plasma. We consider the maximum magnetic field strength to be 60 kGauss (kG) or 6 Tesla (T), but there are some experimental references that use magnetic fields from 5 up to 10 T. [74][75][76] In our scheme, the CO 2 laser pulse [37,39] can provide desired frequencies for incident laser beams. [67] Hematizadeh et al have presented a scheme for THz generation based on the nonlinear mixing of two oblique incident laser beams on an over-dense magnetized plasma; they have also reported generation of THz radiation from under-dense plasma by taking advantage of right-hand circularly polarized (RCP) and left-hand circularly polarized (LCP) waves via different laser beam profiles.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations